Export Prohibition on Cultural Heritage Objects in NIAC: Study of Tangerang City Under Humanitarian Law - Permanasari, Arlina; Nurbaiti, Siti; Notoprayitno, Maya Indrasti; Ramadhan, Nursyahrani Tiara (UNISSULA, 2025)
Protecting cultural heritage during non-international armed conflicts remains a significant challenge for the enforcement of International Humanitarian Law, especially given the rising instances of intentional or accidental destruction of cultural sites in recent decades. This study aims to explores the role of national legal mechanisms and analyzes the legal consequences of cultural heritage preservation, emphasizing its economic aspects. This research applies normative legal methods to analyze a range of international instruments, including the 1954 Hague Convention, the 1999 Second Protocol, and UN Security Council Resolution 2347 (2017), along with soft law sources such as Customary IHL and the 2024 Joint Declaration. The study's results indicate that applying international rules to the Indonesian national legal framework, particularly regarding the prohibition on exporting cultural heritage objects, can serve as a crucial preventive measure. However, at the national level, the Regulation still needs to be strengthened through more technical operational mechanisms, inter-agency cooperation, and the participation of individuals and indigenous peoples, based on international provisions that the world community has accepted.